2007
DOI: 10.1002/ab.20189
|View full text |Cite
|
Sign up to set email alerts
|

Sectioned offenders presenting with enduring mental illness: a study exploring behaviors indicative of bullying

Abstract: Logit and logistic regression analyses were employed to explore the nature, extent and predictors of behaviors indicative of "being bullied" and of "bullying others" in a sample of 125 adult male offender-patients sectioned for enduring mental illness and detained within a high-secure psychiatric hospital. The study addresses the lack of research into this specialized population to date, with a subsidiary aim of comparing the results directly with a previous study conducted with a population of adult male pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(69 citation statements)
references
References 23 publications
5
57
0
7
Order By: Relevance
“…Despite this, the findings are in line with previous research where higher prevalence estimates for indirect aggression have been found in high and medium secure settings (Ireland and Bescoby, 2005;Ireland and Rowley, 2007;Cooper et al, 2011). It is possible that indirect aggression was reported more frequently due to the subtle nature of such behaviours and the likelihood of these going unnoticed in secure settings (Ireland, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Despite this, the findings are in line with previous research where higher prevalence estimates for indirect aggression have been found in high and medium secure settings (Ireland and Bescoby, 2005;Ireland and Rowley, 2007;Cooper et al, 2011). It is possible that indirect aggression was reported more frequently due to the subtle nature of such behaviours and the likelihood of these going unnoticed in secure settings (Ireland, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…It remains unclear how much of bullying is perpetrated by an individual or by a group of individuals. However, it is perceived that the findings reported here are an underestimate of the pure bully group if such individuals are expected to be less likely to engage in treatment and participate in research (Ireland and Rowley, 2007). This is because there are a greater number of patients in the unit who fit this description, further supported by the fact that roughly a third of patients declined to take part in this study.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Kui vaadelda vanglakiusamise ulatust, lähtudes teiste kinni peetavate kiusamise ohvriks langemise (ohvrikäitumise) ja teiste kinnipeetavate kiusa mise (kiusamiskäitumise) ulatusest, siis ilmneb, et keskmiselt 53% kinnipeetavatest on seotud ohvrikäitumisega ja 52% kiusamiskäitu misega (Ireland, 2005a). Otsese vanglakiusamise liikide seas kaldub olema sagedasim verbaalne ja/või psühholoogiline kiusamis ja ohvrikäitumine, kusjuures seksuaalne agressioon osutub kõige vähem sagedaseks (Ireland & Bescoby, 2005;Ireland & Ireland, 2000;Ireland & Power, 2004;Ireland & Rowley, 2007;South & Wood, 2006).…”
Section: Vanglakiusamise Olemus Ja Ulatusunclassified